ANALYSES OF NEWSPAPER EDITORIALS’ LEXICAL RICHNESS RELEASED IN THREE CONCENTRIC CIRCLE NATIONS (Lexeme : Journal of Linguistics and Applied Linguistics, 2022)
The aim of this paper is to look into newspaper editorials in the aspects of their lexical richness authors by editors from three countries that make up the World Englishes concentric circle: native English speaking countries, ESL (English as a Second Language) nations, and EFL (English as a Foreign Language) nations. This paper comprises the production of the Type Token which use editorial articles authored on the exact day in two dominant newspapers from the UK and the US as representatives of UK inner circle nations, two sources from UK outer-circle countries, newspapers from Malaysia and Singapore, and two online newspapers from Indonesia and Thailand as representatives of English For Foreign Language states. The study was based on Laufer and Nation's (1995) vocabulary theory, which highlights the creation of most frequency words lists (K1 and K2 words) and low-frequency word lists (AWL and Off-list words).  The methods used were by uploading text into a vocabulary profiler tool, such as Lexical Frequency Profile (LFP) or a free accessed online platform built by Tom Cobb at http://www.lextutor/ca/vp. The results show that the average number of tokens of off-list words in ESL texts is more diverse rather than in Native and EFL English countries.